Immunohistochemical Evaluation of the Pathological Effects of Diabetes Mellitus on the Major Salivary Glands of Albino Rats - Alqahtani, Mashael Saeed; Hassan, Sherif Sayed (European Journal of Dentistry, 2022)
Objectives Diabetes mellitus is a notorious chronic disease characterized by hyperglycemia. Our study aimed to determine the expression of cytokeratin 17 (CK17) in all major salivary glands of diabetic albino rats to provide more information about the pathological effects of DM on the intracellular structures of the gland parenchyma.Materials and Methods Twenty male adult albino rats were utilized in the experiment and divided into two equal groups, group 1 (control rats) and group 2 (diabetic rats). The animals were sacrificed 45 days after diabetes induction. The major salivary gland complex of all groups was dissected and prepared for evaluation by histological and immunohistochemical expression of CK17.Results Histological results prove that the salivary gland parenchyma of diabetic group undergo gland atrophy characterized with the presence of degenerated acini, dilated duct system, and presence of duct-like structure with predominance of fibrous tissue compartment and discrete fat cells. Immunohistochemical expression of CK17 of major salivary gland of control group revealed negative to diffuse mild expression in all duct cells and some serous acinar cells, whereas mucous acini were negatively stained. On the other hand, major salivary gland parenchyma of diabetic group demonstrated mild to strong expression of duct cells more concentrated at their apical part with moderate to strong expression of some serous acini of diffuse type, whereas mucous acini of both submandibular gland and sublingual gland were negatively stained.Conclusion The severity and prevalence of CK 17 in our results are predictive of the pathological influence of the DM that interferes with saliva production and/or secretion leading to dry mouth. The results also showed clear changes in the cytokeratin expression of diabetic sublingual salivary gland, although it had little effect in the routine histological study with hematoxylin and eosin, confirming that routine studies are not sufficient to form a definitive opinion.
Keywords: parotid gland; sublingual; submandibular; diabetes; cytokeratin 17